2018
DOI: 10.1155/2018/6248047
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Investigation of Organic Wastes of Frying Oils and Beef Fats: Valorization for Biodiesel Production

Abstract: The present study investigates the different approaches of biodiesel production by exploiting low cost feedstocks such as organic wastes of frying oils (WFO) and wastes of beef fats (WBF). The aim was to compare not only two different sources of waste raw materials but also different approaches of biodiesel production. Biodiesel which refers to fatty acid methyl esters (FAME) was produced by both chemical and enzymatic transesterification. The characterization of the biodiesel produced by both approaches was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Authors reported a biodiesel yield of 70% when using waste oil and 90% using soybean oil, which suggested that ultrasound technology and enzyme mixtures could be a promising route to reduce costs of biodiesel production. Souissi et al [25] evaluated the use of two low-cost feedstocks such as WFO and wastes of beef fats to produce biodiesel via both chemical and enzymatic transesterification and reported a richer FAME biodiesel with the biological method. Kumar et al [26] analyzed the feasibility of biodiesel production from hybrid oil using bio-support beads immobilized with lipase from Pseudomonas cepacia.…”
Section: Introductionmentioning
confidence: 99%
“…Authors reported a biodiesel yield of 70% when using waste oil and 90% using soybean oil, which suggested that ultrasound technology and enzyme mixtures could be a promising route to reduce costs of biodiesel production. Souissi et al [25] evaluated the use of two low-cost feedstocks such as WFO and wastes of beef fats to produce biodiesel via both chemical and enzymatic transesterification and reported a richer FAME biodiesel with the biological method. Kumar et al [26] analyzed the feasibility of biodiesel production from hybrid oil using bio-support beads immobilized with lipase from Pseudomonas cepacia.…”
Section: Introductionmentioning
confidence: 99%
“…This experiment showed that the transesterification of low-cost lipid feedstocks with low excess of methanol and without generation of glycerol is technically feasible, and it is likely to be used at an industrial scale. It was also concluded that the thermal decomposition of chicken fat is an important factor; however, it was found that this factor was not significant if heated up to 350 • C. Souissi et al (2018) [78] tested beef fats as raw material for biodiesel production. In this experiment, enzymatic and chemical transesterification were used, and it was concluded that although the biological method allowed them to obtain a FAME-richer biodiesel, by the chemical method, a biodiesel with better physicochemical properties was obtained.…”
Section: Fat Valorisation Systemsmentioning
confidence: 99%
“…The cost of the raw material is a crucial aspect of biodiesel production, corresponding to at least 80% of the total cost of biofuel production (6). Therefore, various studies focus on the utilization of less expensive feedstocks, like non-edible oils, waste cooking oils, and animal fats (7)(8)(9)(10). However, these feedstocks have certain drawbacks, primarily attributed to their high content of free fatty acids (FFA), which are not suitable for the commonly employed homogeneous base-catalyzed transesteri cation process, due to the formation of soap, through the reaction of FFA with the catalyst, leading to catalyst deactivation (11).…”
Section: Introductionmentioning
confidence: 99%